Implikasi Hukum Perjanjian Nominee Antara Warga Negara Asing dan Warga Negara Indonesia dalam Kepemilikan Tanah - Andi Saputra; Amad Sudiro (LPPM Universitas Ekasakti Padang, 2023)
This research discusses the nominee agreement in the context of land ownership by foreign nationals in Indonesia. Despite the Agrarian Basic Law explicitly prohibiting foreigners from owning land, the practice of nominee agreements or lending names is still prevalent. The study compares the validity of nominee agreements in Indonesia with other Asian countries such as Thailand, the Philippines, Malaysia, and Singapore. The research findings indicate that Indonesia lacks specific regulations regarding nominee agreements, while other countries have established clear guidelines. Specific legal cases are also examined, including the legal implications for notaries involved in drafting nominee agreements. The study recommends that the Indonesian government enact stricter regulations concerning nominee agreements to prevent illicit legal practices. It is hoped that more stringent sanctions will be imposed on notaries engaged in nominee agreements. Keywords: nominee agreement, land ownership, foreign nationals, Agrarian Basic Law, illicit legal practices.